1993
DOI: 10.1117/12.161368
|View full text |Cite
|
Sign up to set email alerts
|

<title>Development and characterization of a time-, position-, and energy-resolved x-ray diagnostic for PBFA II target experiments</title>

Abstract: A time-, position-and energy-resolved soft x-ray (100-500 eV) diagnostic is being developed for PBFA II target experiments. The diagnostic provides measurements of hydrodynamic motion and thermal gradients in light-ion fusion targets. A slit-image of the source is imprinted onto thin sheets (20l.tm) of organic scintillator to create a one-dimensional image. The scintillator light is then proximity-coupled to a linear array of fiber-optics that transports the light to a streak camera that is operated without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is a wealth of information about the performance of MCP's. A few of the relevant papers are included in the references (4)(5)(6)(7)(8).…”
Section: Mcpi Characterization and Discussion Of Film As Readout Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wealth of information about the performance of MCP's. A few of the relevant papers are included in the references (4)(5)(6)(7)(8).…”
Section: Mcpi Characterization and Discussion Of Film As Readout Mediummentioning
confidence: 99%
“…',~,~ There is a companion paper to this which includes more information on the motivation and specific usage of these cameras at the Particle Beam Fusion Accelerator II. 4 No tutorials have been found that simplify the coupling of the camera to a readout system or quantify and explain the tradeoffs for individual systems. In addition to this, each streak camera type has its own limitations with respect to sensitivity, photocathode length, resolution and dynamic range.…”
mentioning
confidence: 99%